Fibreoptic injection of oesophageal varices. Issue 6193 (29th September 1979) - Williams, K G; Dawson, J L
Abstract : A new technique for injecting sclerosant into oesophageal varices uses a flexible gastroscope. Once the gastroscope has been inserted a flexible tube with a window cut into its distal end is pushed down over the gastroscope until a varix protrudes through the window. The varix can then be injected with a needle passed down the biopsy channel of the gastroscope. Once the varices have all been injected in this way the tube is advanced to compress the injection sites and so help control bleeding. This method, using a flexible gastroscope, has proved easier and safer than the traditional method using a rigid gastroscope.